Phantom Limb Pain: Low Frequency Repetitive Transcranial Magnetic Stimulation in Unaffected Hemisphere - Andrea Di Rollo; Stefano Pallanti (Case Reports in Medicine)
Phantom limb pain is very common after limb amputation and is often difficult to treat. The motor cortex stimulation is a valid treatment for deafferentation pain that does not respond to conventional pain treatment, with relief for 50% to 70% of patients. This treatment is invasive as it uses implanted epidural electrodes. Cortical stimulation can be performed noninvasively by repetitive transcranial magnetic stimulation (rTMS). The stimulation of the hemisphere that isn't involved in phantom limb (unaffected hemisphere), remains unexplored. We report a case of phantom limb pain treated with 1 Hz rTMS stimulation over motor cortex in unaffected hemisphere. This stimulation produces a relevant clinical improvement of phantom limb pain; however, further studies are necessary to determine the efficacy of the method and the stimulation parameters.